Fake News and Public Perception of Social Media News - Collins Onyema Esiobu; Ifeanyi Martins Nwokeocha; George Nathan Brown; Ifechukwu Nchedo Okoye (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study explored the impact of misinformation on public opinion regarding stories and information on social media, focusing on factors that influence users' perception and engagement. The primary emphasis is on explaining the impact of deception in shaping media outlets' credibility and how deception constructs narratives within society. The study employed the Theory of Rumor Transmission and the Technological Determinism Theory, which explain news diffusion patterns in the online environment and the influence of technology on communication practices. A qualitative research design was adopted. Findings revealed that the consumption of fake news is strongly linked to increased mistrust of traditional media, leading individuals to seek alternative, largely unverified sources. Additionally, the propagation of misinformation is autocatalytic in echo chambers, contributing to heightened polarization of individuals' views. The study concludes that preventing issues arising from fake news is crucial to fostering an educated citizenry. In light of these findings, it is recommended that social media platforms implement strict fact-checking mechanisms, integrate media literacy into school curricula, and establish governance frameworks that hold platforms accountable for the dissemination of disinformation while safeguarding freedom of speech.